2017
DOI: 10.21834/ajqol.v2i5.9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on the Malaysian Food Heritage

Abstract: Traditional food was closely associate with food heritage has become a significant role in the life of society. A study examines how far Malaysian knows about their food heritage identity. A total of 500 respondents located in Klang Valley participate in this study. Findings showed that food heritage been defined as traditional food. There is a significant relationship between genders with the definition of food heritage; the association of food heritage questions. The overall finding revealed that respondent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…As epistemic value is related primarily to novelty, this may indicate a desire for domestic travellers to partake in new or rare experiences related to food. The novelty of Pahang's heritage food may relate to the opportunity for domestic travellers to reconnect to their culinary heritage reaffirming recent findings in the literature (Ramli et al, 2017). The feelings of curiosity and a sense of novelty can significantly influence a tourist's motivation to try Pahang heritage food.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…As epistemic value is related primarily to novelty, this may indicate a desire for domestic travellers to partake in new or rare experiences related to food. The novelty of Pahang's heritage food may relate to the opportunity for domestic travellers to reconnect to their culinary heritage reaffirming recent findings in the literature (Ramli et al, 2017). The feelings of curiosity and a sense of novelty can significantly influence a tourist's motivation to try Pahang heritage food.…”
Section: Discussionsupporting
confidence: 74%
“…Omar et al (2015) referred to heritage food as "typical local culinary, embedded with cultural values that represent the social community lifestyles, traditions or features that have been handed down from one generation to the next." More recently, academic researchers have found that Malaysian consumers view heritage food to be those traditional foods that are passed down from one generation to another and are associated with a region's cultural background and history (Ramli, Zahari, Halim & Aris, 2017). For this study, we consider heritage food to be a local cuisine in nature and adheres to the fundamental traditions, values, and community lifestyles passed down from one generation to the next.…”
Section: Heritage Food In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…These catering concepts and their 'heritage' food products, loaded with cultural references, seem to benefit from this additional clientele. At the same time, tourists' expectations of local and 'authentic' foods are further accelerating the trend towards the patrimonialisation of foods (Poulain, 1997;Bessière, 2008;Bessière, 2018;Bessière & Tibère, 2013;Tibère & Aloysius, 2013;Ramli et al, 2017). This context offers new opportunities for actors in the food industry and the catering sector, enabling them to develop new products and services such as healthy food or foods perceived to have cultural attributes, and to encourage shorter circuits between producers and consumers.…”
Section: A 'Compressed' Modernisation In Malaysiamentioning
confidence: 99%